Social factors of spreading of tobacco smoking among college students - N.V, Lazurenko (2020)
The objective of an empirical study of the social factors of spreading of smoking among college students was to identify the influence of the social environment and lifestyle on the formation of addiction. In our study, we relied on the concept of a value-social model of health. The materials of the study, which included a student survey (n = 495, proportional selection by gender, age, year of study) and a standardized interview with youth professionals (n = 21), analyzed the main motives for smoking youth, attitudes towards a healthy lifestyle, attitude towards smoking peers. A comparative analysis of the data was carried out in subgroups of smoking and non-smoking students. The results of the study showed the lack of formation of negative attitudes to smoking in the vast majority of students. According to 25% of smoking students and 39% of non-smoking students, smoking is one of the tools of communication and integration in the new team. 45.6% of all respondents cited group exposure and conformal behavior as reasons for starting smoking.  The results on assessing attitude to smoking from the perspective of fashion and social recognition turned out to be unexpected: the number of non-smoking students who think that smoking is fashionable is 17 times exceeds the number of smokers who share these beliefs. A comparison of the data indicates a probable reason for this distribution of answers: in everyday life, smokers are faced with various legislative restrictions and social censure, while their non-smoking peers focus on the socio-communicative and recreational effects of this habit. Students demonstrated a high level of awareness of the negative effects of smoking. One fifth of students (20.9% non-smokers and 22.1% smokers) proposed banning tobacco advertising as preventive measures. In the Russian Federation, the ban has been in force since 2013. It can be assumed that the placement of information on the dangers of tobacco consumption works as a trigger, and is perceived as an advertising message by part of the audience. This hypothesis needs further refinement and will be verified by a separate study.